Model of Effective Development of Forestry of Ukraine - Кудряшова, К. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The article reviews the existing models of forestry, defines their main advantages and disadvantages. The model of recycling logging waste and primary processing of wood for the purpose of rational use of forest resources is presented. As a result of study, the model of effective development of forestry of Ukraine was drawn on the basis of not exhaustion and sustainable development. Prospects for further research in this direction are the grounds for efficiency of model of production intensification.